A novel murine model of Sjögren’s disease using lacrimal autoantigen - Li, Siyuan; Liu, Shan; Li, Yaqiong; Zhang, Peng; Lei, Fengyang; Tian, Lei; Jie, Ying (Frontiers in Immunology, 2026)
PurposeSjögren’s disease (SjD) is a group of chronic autoimmune diseases primarily targeting exocrine glands, including the lacrimal glands (LG). Involvement of the lacrimal glands leads to severe dry eye, also known as Sjögren’s disease-associated dry eye (SjD-DE). Current, available animal models of SjD are achieved by using autoantigens from salivary gland. This study establishes a novel lacrimal gland-specific autoimmune model that recapitulates key features of SjD-DE, providing a tool for investigating LG-focused mechanisms in SjD.MethodsTo establish the lacrimal gland-specific Sjögren’s model (termed LGSS) model, autoimmune responses were induced in mice using homogenized lacrimal gland proteins. LGSS mice were evaluated at various timepoints after immunization to determine SjD development. SjD phenotype such as tear and saliva secretion, lymphocyte infiltration in the lacrimal and salivary glands and serum autoantibody levels was assessed. Immune cell profiles in the spleen and cervical lymph nodes were evaluated via flow cytometry. In addition, corneal epithelial intactness, goblet cell density, lacrimal gland injury was evaluated to assess lacrimal gland involvement and secondary ocular surface damage. RNA sequencing and gene enrichment analysis of diseased lacrimal glands were performed.ResultsLGSS mice demonstrated a reduced tear and saliva secretion, increased lymphocyte infiltration, and elevated autoantibody levels that are similar to common SjD mice. Additionally, the established LGSS mice demonstrated increased populations of Th1 and Th17 cell, along with lacrimal gland and ocular surface damage. RNA sequencing revealed that LGSS mice shared a common genetic profile with NOD mice, the spontaneous SjD model, such as Parp9, Cdkn2c, and Ifi35. Additionally, LGSS mice exhibited several uniquely expressed genes, including metabolism-related genes (Cbs, Dlst, Sardh) and genes associated with cellular processes (Actc1, Tnnc1).ConclusionThe LGSS mice have been shown that successfully replicates several key features of SjD and demonstrates significant lacrimal gland and ocular surface damages, making it a valuable animal model to study SjD-DE.